Analysis of Clean Water Services in Dili City Based on Service Ratio - Gomes, Orlando; Wulandari, Esti; Nugroho, Laksono Djoko (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
Adequate availability of clean water is an essential basic need for urban communities, including in Dili City, the capital of Timor Leste, as clean water supports health, hygiene, and various economic activities. However, Dili City faces a number of challenges in providing optimal clean water supply, such as rapid population growth, uncontrolled urbanization, inadequate infrastructure, and a distribution leakage rate of up to 30%, which causes difficulties in accessing clean water for some communities. This study aims to analyze the demand and availability of clean water in Dili City, and calculate the ratio of clean water services based on existing data, using a positivistic approach and theoretical-analytical and empirical-analytical methods. The results show that the demand for clean water in Dili City reaches 129,060 liters per second, with the highest production capacity in Comoro Village, but the distribution of clean water services is not evenly distributed. Becora Village has the highest service ratio, while Balibar Village shows a low ratio.